(untitled) (Actual Problems of Mind, 2022)
The paper presents an overview of the main conceptions and approaches in the field of normative ethics, developed within modern analytical philosophy. Two main types of normative ethical theories are considered — teleological and deontological ones, which differ in defining the concept of right and the concept of good and interpreting relationship between them. Theories of the teleological type (consequentialism and virtue ethics) are characterized by putting good as the primary category of ethics, which is defined independently of other ethical concepts, in particular, what can be considered right and wrong. The category of morally right, on the contrary, is defined in these theories through the concept of good, namely, as something that increases (maximizes) good or contributes to its realization. Thus, the teleological (in a broad sense) approach to ethics assumes the derivation of moral norms, in particular those that determine right behavior, from the concept of good, which acts as some basic (ultimate) goal, the achievement of which is seeking by any moral person. This ultimate and unconditional good does not depend on any moral norms and can be defined in different ways. Based on how the concept of good is concretized, various teleological concepts of normative ethics are possible. In particular, we can distinguish between egoism, altruism and utilitarianism. Both egoism and altruism have their followers among analytical philosophers, but the most widespread is utilitarianism. In theories of the deontological type (ethics of duty), the relationship between the main ethical concepts actually changes to the opposite, namely: the category of moral right is considered as the main and primary one. Accordingly, the good in such theories appears to be a subordinate concept and is ultimately defined through moral norms that enshrine and codify what is considered morally right.